Effects of corporate social responsibility activities on Corporate Image: evidence from food and beverage industry in Amhara Region - Yilkal Andualem Demeke; Jaladi Ravi (Cogent Business & Management, 2024)
AbstractEffects of ‘Corporate Social Responsibility’ activities on Corporate Image: Evidence from the Food and Beverage Industry in the Amhara Region, Ethiopia, is the topic of the researchers’ study. The study’s main goal was to look into how specific ‘Corporate Social Responsibility’ activities affected the corporate Image of a few particular firms. Finding CSR activities that can enhance a company’s Image, learning what CSR activities consumers believe are sufficient to meet the criteria for being socially responsible, and pinpointing tactics that encourage a positive Corporate Image of the organizations were among the study’s crucial specific goals. Both primary and secondary sources of information were employed to complete this study. Moreover, five food and beverage processing companies were chosen as a sample using a multi-stage selection methodology. Based on the judgmental sampling technique, the researcher selected 385 sample respondents. The characteristics that affect the corporate Image of food and beverage companies in the research region were investigated using structural equation modelling using SPSS software version 26 and Amos 23. Our findings add to past research that has primarily looked at the direct relationship between CSR activities and Corporate Image. The results showed a substantial direct effect of CSR activities, Economic, Ethical, Legal, and Philanthropic responsibilities on Corporate Image.